Intrauterine Condom Tamponade in Management of Post Partum Haemorrhage - Pandey, S; Amatya, S; Thapa, K; Malla, B (Journal of Nepal Health Research Council, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: Uterine tamponade is often used to control post partum hemorrhage. Among various methods, condom Foley’s catheter tamponade is simple, easy to use and is believed to be effective. The study evaluates outcome of condom Foley’s catheter tamponade. Results: The condom tamponade stopped bleeding in all the cases. Average amount of blood loss was 1221ml. No complications were noted. Methods: In this prespective observational study, condom tamponade was applied to fourteen cases with varying degrees of PPH, not controlled with pharmacologic measures. The efficacy on control of bleeding was assessed along with the total amount of blood loss and any complications. Conclusions: Thus, condom tamponade is an effective method to control intractable PPH. It’s simple and does not require expertise to use, so, it can have a wide application even in resource poor settings. Key words: condom tamponade, intrauterine, post partum haemorrhage